2018
DOI: 10.1556/1886.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection and a history of surgery: A case control seroprevalence study

Abstract: We determined the association between having a history of surgery and the seroreactivity to T. gondii. An age- and gender-matched case-control study of 391 subjects with a history of surgery and 391 subjects without this history was performed. Sera of subjects were analyzed for detection of anti-T. gondii immunoglobulin G (IgG) and M (IgM) antibodies using enzyme-linked immunoassays. Anti-T. gondii IgG antibodies were found in 25 (6.4%) of the 391 cases and in 21 (5.4%) of the 391 controls (odds ratio [OR] = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…3 However, individuals who develop toxoplasmosis, the disease caused by T. gondii , may present several well-recognized clinical features: lymphadenopathy, chorioretinitis, and meningoencephalitis. 4,5 In addition, infection with T. gondii has been associated with heart disease, 6,7 schizophrenia, 8,9 depression, 10,11 and mixed anxiety and depression. 12 Immunocompromised individuals infected with T. gondii may develop disseminated and life-threatening disease.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, individuals who develop toxoplasmosis, the disease caused by T. gondii , may present several well-recognized clinical features: lymphadenopathy, chorioretinitis, and meningoencephalitis. 4,5 In addition, infection with T. gondii has been associated with heart disease, 6,7 schizophrenia, 8,9 depression, 10,11 and mixed anxiety and depression. 12 Immunocompromised individuals infected with T. gondii may develop disseminated and life-threatening disease.…”
Section: Introductionmentioning
confidence: 99%
“…Blood transfusion and organ transplantation have also been mentioned as possible infection risk factors (3). This parasite can lead to chronic infection in individuals, serious problems and death in immune compromised patients, hydrocephalus in congenitally infected newborns, intrauterine fetal death, and spontaneous abortion during pregnancy (4).Several studies found a positive correlation between toxoplasmosis with schizophrenia (5), and depression (6).…”
Section: Introductionmentioning
confidence: 99%